2009
DOI: 10.3892/ijmm_00000310
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction of human leukemia cells by Streptomyces sp. SY-103 metabolites through activation of caspase-3 and inactivation of Akt

Abstract: Abstract. We isolated 23 marine actinomycetes from seawater samples. Of these, strain SY-103 exhibited the strongest cytotoxic activity on human leukemic cell lines. Biochemical tests and 16S rDNA sequencing of this strain allowed us to identify SY-103 as a strain of the genus Streptomyces. In the present study, the pure cytotoxic compound (PCC) from Streptomyces sp. SY-103 metabolites was purified by reversephase HPLC and the biochemical mechanisms of PCCinduced apoptosis in cultured human leukemic cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, this sequential cascade triggers several proteases including caspase-1, -3, and -9. [44][45][46] Caspase-3 (CASP3) also activates the pathway of several enzymatic events and serves as the promoter of apoptosis. [47] In the present study, compounds 4a and 4c induced p53 and BAX gene expression and decreased expression levels of BCL2;…”
Section: The Effects Of Compounds 4a 4b and 4c On Apoptosis Genesmentioning
confidence: 99%
“…Moreover, this sequential cascade triggers several proteases including caspase-1, -3, and -9. [44][45][46] Caspase-3 (CASP3) also activates the pathway of several enzymatic events and serves as the promoter of apoptosis. [47] In the present study, compounds 4a and 4c induced p53 and BAX gene expression and decreased expression levels of BCL2;…”
Section: The Effects Of Compounds 4a 4b and 4c On Apoptosis Genesmentioning
confidence: 99%
“…SY-103 have strong cytotoxic effects which induce apoptosis in human leukemia cells through the activation of caspase3 and inactivation of Akt signaling. 10,11 Recently, it was indicated that ether extracted metabolites of Streptomyces Levis ABRIINW111 have anti-carcinogenic effects on colon cancer 12 as well. Apoptosis was used as a target for cancer therapy and several drugs were designed to activate Caspase family.…”
Section: Introductionmentioning
confidence: 99%